Mechanisms of the prevention and inhibition of the progression and development of non‐alcoholic steatohepatitis by genetic and pharmacological decoy receptor 3 supplementation. Issue 12 (24th March 2017) - Lee, Pei‐Chang; Yang, Ling‐Yu; Wang, Ying‐Wen; Huang, Shiang‐Fen; Lee, Kuei‐Chuan; Hsieh, Yun‐Cheng; Yang, Ying‐Ying; Hsieh, Shie‐Liang; Hou, Ming‐Chih; Lin, Han‐Chieh; Lee, Fa‐Yuah; Lee, Shou‐Dong
Abstract : Aims: Treatment of non‐alcoholic steatohepatitis (NASH) is difficult due to the absence of a proven treatment and its comprehensive mechanisms. In the NASH animal model, upregulated hepatic inflammation and oxidative stress, with the resultant M1 polarization of macrophages as well as imbalanced adipocytokines, all accelerate NASH progression. As a member of the tumor necrosis factor receptor superfamily, decoy receptor 3 (DcR3) not only neutralizes the death ligands, but also performs immune modulations. In this study, we aimed to investigate the possible non‐decoy effects of DcR3 on diet‐induced NASH mice. Methods: Methionine‐ and choline‐deficient (MCD) diet feeding for 9 weeks was applied to induce NASH in BALB/c mice. Decoy receptor 3 heterozygous transgenesis or pharmacological pretreatment with DcR3a for 1 month were designed as interventions. Intrahepatic inflammatory status as well as macrophage polarization, oxidative stress, and steatosis as well as lipogenic gene expression and fibrotic status were analyzed. Additionally, acute effects of DcR3a on HepG2 cells, Hep3B cells, and primary mouse hepatocytes in various MCD medium‐stimulated changes were also evaluated. Results: Both DcR3 genetic and pharmacologic supplement significantly reduced MCD diet‐induced hepatic M1 polarization. In addition, DcR3 supplement attenuated MCD diet‐increased hepatic inflammation, oxidative stress, adipocytokine imbalance, steatosis, and fibrogenesis. Moreover, acute DcR3a incubation in HepG2 cells, Hep3B cells, and mouse hepatocytes could normalize the expression of genes related to lipid oxidation along with inflammation and oxidative stress. Conclusion: The ability of DcR3 to attenuate hepatic steatosis and inflammation through its non‐decoy effects of immune modulation and oxidative stress attenuation makes it a potential treatment for NASH.